Calculation of Heat of Adsorption of Gases and Refrigerants on Activated Carbons from Direct Measurements Fitted to the Dubinin–Astakhov Equation - Kandadai Srinivasan; Pradip Dutta; Kim Choon Ng; Bidyut Baran Saha (Adsorption Science & Technology)
The heat of adsorption of methane, ethane, carbon dioxide, R-507a and R-134a on several specimens of microporous activated carbons is derived from experimental adsorption data fitted to the Dubinin–Astakhov equation. These adsorption results are compared with literature data obtained from calorimetric measurements and from the pressure–temperature relation during isosteric heating/cooling. Because the adsorbed phase volume plays an important role, its dependence on temperature and pressure needs to be correctly assessed. In addition, for super-critical gas adsorption, the evaluation of the pseudo-saturation pressure also needs a judicious treatment. Based on the evaluation of carbon dioxide adsorption, it can be seen that sub-critical and super-critical adsorption show different temperature dependences of the isosteric heat of adsorption. The temperature and loading dependence of this property needs to be taken into account while designing practical systems. Some practical implications of these findings are enumerated.